2021
DOI: 10.2147/vhrm.s319161
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Lipid Profile Abnormalities Among Patients with Metabolic Syndrome in Southwest Ethiopia: A Cross-Sectional Study

Abstract: Background: Lipid profile abnormalities are an integral part of metabolic syndrome (MetS) and major underlying causes of cardiovascular disease (CVD) and type-2 diabetes mellitus (T2DM). Lipid profile abnormalities in a patient with MetS are resulted due to the presence of central obesity and insulin resistance. In Ethiopia, the burden and predictors of lipid profile abnormalities in a patient with MetS are not well known. Thus, this study aimed to determine the prevalence of lipid profile abnormalities and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 46 publications
2
11
4
Order By: Relevance
“…The most important MetS biomarkers in our study were the increased PRO/ANTI_AI, Castelli risk index 1, and TG, as well as lower HDLc levels. These findings are consistent with previous reports that MetS is associated with increased TC, TG, Castelli risk index 1, and decreased HDLc (Haile et al, 2021; Kawamoto et al, 2011; Paredes et al, 2019). Other studies have found that MetS is associated with increased ApoB and decreased RCT (Lim et al, 2015; Sviridov et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…The most important MetS biomarkers in our study were the increased PRO/ANTI_AI, Castelli risk index 1, and TG, as well as lower HDLc levels. These findings are consistent with previous reports that MetS is associated with increased TC, TG, Castelli risk index 1, and decreased HDLc (Haile et al, 2021; Kawamoto et al, 2011; Paredes et al, 2019). Other studies have found that MetS is associated with increased ApoB and decreased RCT (Lim et al, 2015; Sviridov et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…It was seen that the second most common lipid abnormality was a higher level of TC. A study conducted in Southwest Ethiopia reported that the most prevalent lipid abnormality was low HDL with 67.2% and high TC with 44.6% prevalence as the second most prevalent parameter [ 20 ]. Another study reported that a high level of TC was the third most common abnormality [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…24 Hypertension and high blood glucose levels also play a vital role as independent predictors of dyslipidemia in patients with metabolic syndrome. 25 These findings strengthen the recommendation for a comprehensive blood examination of patients with one of the disorders of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 56%